PENGARUH PELATIHAN DAN PROMOSI JABATAN TERHADAP KINERJA KARYAWAN OUTSOURCING DI PT GARUDA INDONESIA (Persero) Tbk - Agus Yulistiyono; Solahudin Solahudin (JMB : Jurnal Manajemen dan Bisnis, 2019)
This study aims to determine: (1) The effect of training on theperformance of outsourcing employees at PT Garuda Indonesia (Persero)Tbk, (2) The effect of job promotions on the performance of outsourcingemployees at PT Garuda Indonesia (Persero) Tbk, (3) Effects of trainingand promotion position on the performance of outsourcing employees atPT Garuda Indonesia (Persero) Tbk.The results show that: (1) Traininghas a positive effect on the performance of outsourcing employees at PTGaruda Indonesia (Persero) Tbk, this can be seen from the results ofsimple regression analysis that addresses projections the higher thevalue of training at a certain value, the higher the value employeeperformance at a certain value (2) job promotion has a positive effecton the performance of outsourcing employees at PT Garuda Indonesia(Persero) Tbk, this can be seen from the results of simple regressionanalysis that addresses projections the higher the value of promotion ata certain value, the higher also the value of employee performance at acertain value (2) Training and job promotion have a positive effect onthe performance of outsourced employees at PT Garuda Indonesia(Persero) Tbk, this can be seen from the results of multiple regressionanalysis, which proves the higher the value of training and promotion atcertain values, mak a the higher the value of employee performance ata certain value